MODIFIKASI PENGOLAHAN DURIAN FERMENTASI (TEMPOYAK) DAN PERBAIKAN KEMASAN UNTUK MEMPERTAHANKAN MUTU DAN MEMPERPANJANG UMUR SIMPAN - Rapeka Reli, Endang Warsiki, dan Mulyorini Rahayuningsih (Department of Agroindustrial Technology, Bogor Agricultural University, 2017)
Tempoyakis one of traditional food that has short shelf life. The pasteurization and packaging improvement could be expected can maintain the quality and extend the tempoyak’s shelf life. This research used polyethylene terephtalate (PET) and polyamide as packaging materials; with modified atmosphere packaging (MAP), non MAP, vacuum and non vacuum. The parameters quality of tempoyak were observed by value of pH, sugar content, lactic acid, alcohol, lactic acid bacteria growth and total plate count. The result showed that the best quality of tempoyak was produced by product with pasteurization treatment. Lactobacillus genus with L.plantarum, L. casei, and L. fermentum were the dominant species of lactic acid bacteria. The result also showed that after the tempoyak was fermented during 84 hours, then the pasteurization should be conducted to stop the fermentation. The 84th hours was a constant phase in which that was the right time to inhibit the acid lactic bacteria growth. Pasteurized tempoyak packaged in PET with MAP technique had the longest shelf life as much as 84 days than others treatment whose had aboutonly 14 untill 56 days. The decreasing of tempoyak quality at 84 days was showed by colour change of tempoyak from yelowness to brown, pH decreased from 3.97 to 3.73, lactic acid content decreased from 1.49% to 0.99%, sugar content decreased from 16.57% to 3.28%, alcohol content of 0.32%, number of lactic acid bacteria decreased from 174.3×104cfu/g to 8.6×102 cfu/g, and total plate count from 177×104 cfu/g to 182.3×103 cfu/g.Keywords: modified atmosfir packaging, pasteurization, tempoyak, vacuum